Analysis Of Muscle Activity Using Surface Electromyography For Muscle Performance In Manual Lifting Task - Halim, Isa; Omar, Noor Rawaida; Kamat, Seri Rahayu; Abdullah, Rohana; Saptari, Adi; Othman, Mohd Shahrizan (Trans Tech Publications, 2014)

(untitled)
In industries, manual lifting is commonly practiced even though mechanized material handling equipment are provided. Manual lifting is used to transport or move products and goods to a desired place.Improper lifting techniquescontribute to muscle fatigue and low back pain that can lead to work efficiency and low productivity.The objective of this study were to analyze muscle activity in the left and right Erector Spinae, and left and right Biceps Brachii of five female subjects while performing manual lifting taskwithdifferent load mass, lifting height and twist angle.The muscle activitywere measured and analyzed using surface electromyography (sEMG).This study found that the right Biceps Brachii, right and left Erector Spinae experienced fatigue while performingasymmetric lifting (twist angle = 90°) at lifting height of 75 cm and 140 cm with load mass of 5 kg and 10 kg. Meanwhile, the left Biceps Brachii experienced fatigue when the lifting task was set at lifting height of 75 cm, load mass of 5 kg and twist angle of 90°.The load mass and lifting height has a significant influence to Mean Power Frequency (MPF) for left Biceps Brachii,left and right Erector Spinae. This study concluded that reducing the load mass can increase the muscles performance which can extend the transition-to-fatigue stage in the left and right Biceps Brachii and Erector Spinae.